Calibrating CII RT283’s Modularization Critical Success Factor Accomplishments - Choi, Jin Ouk; O’Connor, James T.; Kwak, Young Hoon; Ghimire, Rajarshi (Modular and Offsite Construction (MOC) Summit Proceedings, 2019)
Modularization is a well-known construction technique where sections of the job are moved from on-site to a fabrication shop. Previously, the researchers identified the 21 most influential Critical Success Factors (CSFs) for successful modularization and quantified the degree of each CSF’s accomplishment by conducting a survey with 19 subject matter experts, and a case study with three modular projects. Through this methodology, the findings relied on the experience of experts. However, still missing from the understanding of modularization CSFs is a validation of the current degree of each CSF’s accomplishment by examining actual modular projects using a sufficient number of samples. This paper presents a comparison of CSF accomplishment degree between 25 actual sample projects (project based) and the industry experts’ survey results (experience-based estimation). The study results indicate that the industry experts made a good estimation of the current occurrence degree of each CSF. The study did identify, however, three significantly overestimated CSFs and three underestimated CSFs. The three most overestimated CSFs are Owner-Furnished/Long Lead Equipment Specification, Cost Savings Recognition, and O&M Provisions. The three most underestimated CSFs are Contractor Experience, Management of Execution Risks, and Transport Delay Avoidance. This study will help the industry to 1) better understand modularization CSFs and their accomplishment statuses; 2) achieve higher modular project performance by accomplishing the CSFs